Assessing user perceptions of the interplay between the sharing, access, platform and community‐based economies. Issue 3 (21st February 2020) - Geissinger, Andrea; Laurell, Christofer; Öberg, Christina; Sandström, Christian; Suseno, Yuliani
Abstract : Purpose: Digitally intermediated peer-to-peer exchanges have accelerated in occurrence, and as a consequence, they have introduced an increased pluralism of connotations. Accordingly, this paper aims to assess user perceptions of the interplay between the sharing, access, platform, and community-based economies. Design/methodology/approach: The sharing, access, platform, and community-based economies have been systematically tracked in the social media landscape using Social Media Analytics (SMA). In doing so, a total material of 62, 855 publicly posted user-generated content concerning the four respective economies were collected and analyzed. Findings: Even though the sharing economy has been conceptually argued to be interlinked with the access, platform, and community-based economies, the empirical results of the study do not validate this interlinkage. Instead, the results regarding user perceptions in social media show that the sharing, access, platform, and community-based economies manifest as clearly separated. Originality/value: This paper contributes to existing literature by offering an empirical validation, as well as an in-depth understanding, of the sharing economy's interlinkage to other economies, along with the extent to which the overlaps between these economies manifest in social media.